g. 909 - 909 (102 - 909:9+ 0 : 1) - 99 (9 x 9:9-9)
h. 3x (6 - 6:2) + 305:5+ (100:5+ 8 x 5 x 0): 5
i. 138 + (27:3-1) 2:8 +2 x (100 - 195 : 15) x
î. 7 + 7:7* (7-7:7) 7:7
j. (202:2 + 101 x 2):3-2 (2-2:2)
k 36 + 8x (100 - 47 - 53 +2×18): (13- 36:9)
Răspunsuri la întrebare
Răspuns de
4
Explicație pas cu pas:
g. 909 - 909 (102 - 909:9+ 0 : 1) - 99 (9 x 9:9-9) =
909-909(102-101+0)-99×0=
909-908=1
h. 3x (6 - 6:2) + 305:5+ (100:5+ 8 x 5 x 0): 5 =
3×3+61+(20+0):5=70+4=74
i. 138 + (27:3-1) 2:8 +2 x (100 - 195 : 15) =
138+8×2:8+2(100-13)=
138+2+2×87=138+174=312
î. 7 + 7:7* (7-7:7) 7:7=7+(7-1)7:7=7+42:7=
7+6=13
j. (202:2 + 101 x 2):3-2 (2-2:2) =
(101+202):3-2=303:3-2=101-2=99
k) 36 + 8x (100 - 47 - 53 +2×18): (13- 36:9) =
36+8(100-100+36):(13-4)=
36+8×36:9=36+8×4=36+32=68
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă